Association between emotional distress and the efficacy of advanced gastric cancer patients undergoing treatment with immune checkpoint inhibitors: a cohort study and propensity score matching study - Tian, Ruoxi; Wang, Siqi; Ji, Zhengzheng; Li, Jiasong; Zhang, Jingjing; Zhang, Shasha; Guo, Zhanjun (Frontiers in Oncology, 2025)
BackgroundCancer patients are at a greater risk of experiencing emotional distress (ED) compared to individuals without cancer, with those diagnosed with gastric cancer (GC) exhibiting a higher prevalence of ED than patients with other types of malignancies. A meta-analysis showed that 37% of global GC patients had depressive symptoms. Numerous studies have demonstrated that ED can lead cancer patients to develop immunosuppressive tumor microenvironments (TME), thereby impairing the exertion of antitumor immune effects. Currently, there is a lack of research investigating the correlation between ED and outcomes in GC patients undergoing treatment with immune checkpoint inhibitors (ICIs). We conducted a prospective cohort study to explore the correlation between ED and tumor response as well as prognostic outcomes in patients with advanced gastric cancer(AGC) who received ICIs treatment.MethodsWe prospectively enrolled 104 patients with AGC undergoing combination therapy with ICIs, of whom 46 (44.2%) exhibited ED, defined as symptoms of depression (Patient Health Questionnaire-9 score ≥5) and/or anxiety (Generalized Anxiety Disorder 7-item scale score ≥5) at baseline. The Response Evaluation Criteria in Solid Tumors (RECIST v1.1) criteria were employed to evaluate tumor response. We analyzed the correlation between ED and outcomes including overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR).ResultsBaseline ED was associated with a higher risk of death (HR: 2.035, 95%CI:1.272-3.254, P=0.003) and higher risk of progression (HR: 3.006, 95%CI: 1.922-4.701, P<0.001), as well as a lower DCR (RR: 0.504, 95%CI: 0.343-0.742,P=0.001), in AGC patients undergoing ICIs therapy. Cox multivariate analysis and propensity score matching (PSM) still indicated a significant correlation between ED status and survival outcomes. The baseline ED was not significantly correlated with cortisol levels with a HR of 2.318 (95% CI: 0.805-6.679, P=0.119). Patients exhibiting baseline depressive symptoms was correlated with reduced OS (HR: 2.231, 95%CI: 1.396 - 3.564, P=0.001) and PFS (HR: 2.488, 95%CI: 1.590 - 3.891, P<0.001) following ICIs therapy. After two cycles of treatment, the new onset of ED was found to have a worse survival prognosis compared to those who had never experienced ED (HR: 2.813, 95%CI: 1.270-6.228, P=0.011).ConclusionsED is associated with worse outcomes in AGC patients undergoing treatment with ICIs.